HUBUNGAN ANTARA ANDROGINITAS DENGAN TOLERANSI SOSIAL PADA WANITA PENGHUNI PEMUKIMAN PADAT DI KOTA YOGYAKARTA - Indra Wahyudi (Jurnal Psikologi, 2016)
Forty seven respondents participated in this research. They lived at the densest area at the Danurejan sub-district in Yogyakarta. Objective of this research is to verify the relationship between people’s androgyny and their social tolerance. The dense kampong is the most favorite area for urban poor people to live. However, living at the high density areas is really stressful. People have to adapt with the inconvenience living arrangements. The best strategy to make harmonious adaptation is having social tolerance among neighbors. Androgyny is perceived as the best attitude in facing difficult situation. Androgyny is a fusion between feminine and masculine attitudes. Therefore hypothesis of this research is that there is a positive relationship between people’s androgyny attitude and their social tolerance. This research revealed that there was positive relationship between those two variables (r = .508, p<.01).